2020
DOI: 10.1088/1755-1315/426/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Modelling progressive failure of steel moment frames exposed to localised fire

Abstract: This paper presents modelling of the progressive failure of steel moment frames subjected to localised fire. A finite element approach using the software ABAQUS has been developed to analyse the structure. An explicit-dynamic solution was adopted to solve the non-convergence problems caused by element buckling. A series of validation analyses were carried out to ensure that the results were within an acceptable level of accuracy. The analysis results are shown to match well with the previous experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the parameters affecting the structural robustness in a fire have not yet been explored. To address this gap, this study extends previous work by Suwondo et al (2019) on modelling progressive failure of multi-storey steel moment frames exposed to fire. The modelling approach is adopted to undertake parametric studies to identify effective methods to improve the robustness of such structures under fire conditions.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the parameters affecting the structural robustness in a fire have not yet been explored. To address this gap, this study extends previous work by Suwondo et al (2019) on modelling progressive failure of multi-storey steel moment frames exposed to fire. The modelling approach is adopted to undertake parametric studies to identify effective methods to improve the robustness of such structures under fire conditions.…”
Section: Introductionmentioning
confidence: 86%
“…The simulations showed that ignoring the dynamic effect may produce lower displacement of the structure and lead to less conservative design. Suwondo et al (2019) performed progressive collapse analysis of composite building under fire following an earthquake. Initially, the analysis of the undamaged building was performed to study load redistribution path and members' interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation